Peran Guru Pendidikan Agama Katolik dalam Meningkatkan Keterampilan Sosial Peserta Didik SMA Swasta Santa Maria Kabanjahe - Mimpin Sembiring; Abdi Guna Sitepu; Aser Wiro Ginting; Paulinus Tibo (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
Social skills are skills that need to be possessed by every student because these social skills are part of life skills. Social skills can also require students to achieve success in their social life at school and in society. Good student life and association can foster students' social skills. Through these social skills, students will be able to relate and respond to other people well. This research was conducted to examine the role of Catholic Religious Education teachers in improving the social skills of Santa Maria Kabanjahe Private High School students with 12 informants consisting of: Catholic Religious Education Teachers, Principals and students. This research uses qualitative research. Research data obtained by means of observation, interviews and documentation. This research took place from March to May 2021. The results showed that the role of Catholic Religious Education teachers had been carried out as well as possible in improving students' social skills, students at Santa Maria Kabanjahe Private High School had good social skills through the role of Catholic Religious Education teachers who include: the role of Catholic Religious Education teachers as role models, as learning managers, as motivators, and as curriculum implementers